2010
DOI: 10.4049/jimmunol.0902667
|View full text |Cite
|
Sign up to set email alerts
|

IL-32: A Host Proinflammatory Factor against Influenza Viral Replication Is Upregulated by Aberrant Epigenetic Modifications during Influenza A Virus Infection

Abstract: Material Supplementary 7.DC1http://www.jimmunol.org/content/suppl/2010/10/01/jimmunol.090266References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
107
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 40 publications
8
107
2
2
Order By: Relevance
“…Earlier studies have revealed that promoter hypermethylation suppresses gene expression, since up-methylated CpG sites may block the combination of active transcription factors (TFs) at the binding site (Li et al, 2010;Wang et al, 2010). Using the TFSEARCH software, three active TFs (ADR1, GATA-1 and GATA-2) were predicted to be located at the CpG sites of the bovine CD4 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have revealed that promoter hypermethylation suppresses gene expression, since up-methylated CpG sites may block the combination of active transcription factors (TFs) at the binding site (Li et al, 2010;Wang et al, 2010). Using the TFSEARCH software, three active TFs (ADR1, GATA-1 and GATA-2) were predicted to be located at the CpG sites of the bovine CD4 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation analysis. Previous studies of CpGs in the promoter regions of the interleukin-6 gene (IL-6) and IL-32 suggest that these can be demethylated due to inhibition of Dnmts during influenza A virus infection (31,32). We therefore investigated if the relative levels of transcripts encoding three different enzymes (Dnmt1, Dnmt3a, or Dnmt3b) and transcripts encoding ERVWE1, IL-6, or IL-32 were altered in response to influenza A/WSN/33 virus infection in a neuronal epithelioma cell line (SK-N-MC), a lung carcinoma cell line (A549), a kidney epithelioma cell line (293A), or primary fibroblasts.…”
Section: Regulation Of Herv-w Transcription By Influenza A/wsn/33 Virmentioning
confidence: 99%
“…An increasing body of literature suggests that viral infections can modify the methylation status of host DNA in cells of rat and human origin (27)(28)(29)(30). Recent publications suggest that influenza A virus can cause CpG demethylation by interfering with DNA methyltransferase (Dnmt) activity (31,32). In addition, a DNA methylation-independent pathway has been reported in the proviral silencing of endogenous retroviruses (ERVs) in mouse embryonic stem cells (mESCs) through trimethylation of H3K9 (33).…”
mentioning
confidence: 99%
“…This synergistic effect may result from removal of the inhibitory effect of promoter methylation coupled with transcriptional activation by transcription factors, like influenza virus. 32,36 Since our results did not reveal changes in MIR23A-5p promotor CpG methylation, expression of this miRNA may be regulated by other mechanisms, rather than epigenetic alteration in response to B. pseudomallei infection. Taken together, we concluded that the increased expression of MIR4458, MIR4667-5p, and MIR4668-5p observed in A549 cells was attributed to specific alteration in methylation of promoter CpG islands caused by B. pseudomallei infection.…”
Section: Discussionmentioning
confidence: 86%
“…31 Influenza virus specifically regulates the expression of IL6 and IL32 by promoter demethylation. [32][33] Helicobacter pylori has also been found to regulate PTGS2 gene activation by dynamic changes of CpGs methylation at the PTGS2 promoter. 34 In addition, H. pylori-associated DNA methylation alteration occurs to CpG islands of miRNA genes, which leads to change in expression of a subset of host miRNAs.…”
Section: Discussionmentioning
confidence: 99%